Amorphous Silicon (a-Si:H)/Silicon Nitride (a-SiNx:H) Superlattice by D.C Plasma Enhanced Chemical Vapour Deposition: Preparation and Characterisation - Ibrahim Mitani, Sufian Mousa (Malaysian Journal of Science, 2005)
Amorphous Silicon (a-Si:H)/Silicon Nitride (a-SiNx:H) Superlattice by D.C Plasma Enhanced Chemical Vapour Deposition: Preparation and Characterisation